CD95L mediates tumor counterattack in vitro but induces neutrophil-independent tumor rejection in vivo - Igney, Frederik; Behrens, Christian; Krammer, Peter H. (International journal of cancer, 2005)
Many tumors express CD95L (CD178, FasL, APO-1L) and may thus kill tumor-infiltrating lymphocytes, a phenomenon called tumor counterattack. However, presently it is not clear whether tumor counterattack is a relevant immune escape mechanism. To characterize the effect of CD95L expression of tumor cells on tumor-specific T cells, we established an in vitro system with TCR tg T cells and a model tumor antigen. Preactivated antitumor T cells were able to kill CD95L− and CD95L+ tumor cells. CD95L+ tumor cells killed activated T cells in vitro and inhibited the expansion of cytotoxic antitumor T cells in mixed lymphocyte tumor reactions. In vivo CD95L expression led to delayed tumor growth or complete tumor rejection. Neutrophils were not responsible for the delayed growth of the CD95L+ tumors tested. In mice with neutrophils deficient for important cytotoxicity mechanisms (p47phox−/− or iNOS−/− mice), CD95L+ tumors grew similarly as in wild-type mice. Incidence and growth rate of CD95L+ tumors in mice injected with a neutrophil-depleting or an isotype control antibody was the same. In CD95-deficient lpr mice, tumor growth was not altered as compared to wild-type mice. Taken together, CD95L mediated tumor counterattack in vitro, but led to neutrophil-independent tumor rejection in vivo.
First published: 25 August 2004
Gesehen am 04.03.2021